Influence of urban development on change in microclimatic parameters of urbanized area. Issue 1 (April 2021) - Bulgakov, A; Skobeleva, E
Abstract: The expediency of quantitative analysis of safety and comfort of the spatial environment when creating master plans of cities was shown by the authors. Predictable thermal comfort should be considered here as one of the significant indicators of the environmental safety of the routes from places of residence to socially significant facilities and recreational zones. It is suggested to use thermal indexes adapted for the conditions of open urban spaces to consider the influence of climatic variables totality on the person's thermal sensation. The physiologically effective temperature (PET) is one such index. This model takes visceral temperature, perspiration rate, the moisture of the skin, and on the other hand the meteorological parameters, including the influence of urban area conditions on them. Criteria values of PET for the middle zone of Russia are determined on the basis of bioclimatic estimation of the territory according to air temperature, cloudiness and wind speed. The authors determined experimentally the parameters of the urban microclimate.